STUDY OF CORROSION INHIBITION OF PURE IRON IN LIQUID Pb AND PbBi COOLANT OF FAST REACTOR BY MOLECULAR DYNAMICS SIMULATION METHOD - ARKUNDATO (NIM : 30208004); Tim Pembimbing : Prof. Dr.Eng. Zaki Su‘ud; Prof. Dr.Eng. Mik, ARTOTO
Liquid-metal cooled fast reactors are advanced type of nuclear reactor designs where the primary coolants is a liquid metals. These reactors can be operated for long time period, allow much higher power density than traditional coolants and allow concept of inherent safety in design. For fast reactor, the lead and lead-bismuth are potential candidates for coolant material, having favorable chemical and physical properties including low melting point, low vapor pressure and chemical inertness. However it is also well known that steels used in the core of reactor are highly corroded if exposed to liquid lead or lead-bismuth coolant directly at high temperatures. Then corrosion problem need to be solved immediately. Meanwhile many corrosion experiments have been done, however a complete understanding about corrosion process and how to handle are still unsolved. In this research we investigate the mechanism and the way of reducing the corrosion computationally. We studied the corrosion by using the molecular dynamics simulation method. The simulation method was employed to predict the corrosion properties of material (iron) and to find a way of reducing the corrosion. We regarded the corrosion was a degradation phenomena of material. We modeled the corrosion as a result of high dissolution of iron atoms in interaction with liquid lead and lead-bismuth. Using molecular dynamics simulation we studied the corrosion microscopically, observing the dynamics of interacting atoms of materials (iron, lead, bismuth) during corrosion process. The corrosion analysis was done by calculating the diffusion coefficient of iron and using the CNA (common neighbor analysis) method to examine the structure stability of iron. From simulation results we concluded, in order to reduce the corrosion significantly, oxygen atoms should be injected into liquid lead and liquid lead-bismuth coolant with certain small concentrations. The oxygen should be injection within the range of lower threshold LT = 5.35 x 10-2 wt% and upper threshold UT = 8.95 x 10-2 wt% for the case of liquid lead corrosion, and within the range of LT = 5.32 x 10-2 wt% and upper threshold UT = 11.56 x 10-2 wt% for the case of liquid lead-bismuth corrosion. The oxygen injection within that range will develop a protective self-healing iron oxide layer at the surface of iron to protect the iron from high corrosion. The oxygen injection also creates a barrier that separates the inner wall of liquid metal coolant from the surface of iron. The injection of oxygen at content of 5.35 × 10-2 wt% may reduce the corrosion till 96.76% for the case of iron in lead coolant whereas the injection of 5.32 × 10-2 wt% oxygen may reduce the iron corrosion rate till 92.16% for the case of iron in lead-bismuth coolant, at temperature 750 oC.